Magnetic States of the Co-ions in Ca and Y Doped (Bi,Pb)2Sr2Co2O8 Thermoelectric Materials - Inge M. Sutjahja; A. A. Nugroho (Institute for Research and Community Services (LPPM) ITB, 2012)
The magnetic states of Cobalt ions in magnetic thermoelectric materials of Bi1.5Pb0.5Ca2-zYzCo2O8 (z = 0, 0.1, 0.2, and 0.3) have been studied from the structural (X-ray diffraction) and magnetic susceptibility data. The misfit structure was revealed from refinement of the XRD data, with reduction of the lattice parameters while increasing the Y doping content. Compared with the (Bi,Pb)2Sr2Co2O8 parent compound system, the lattice parameter c was reduced significantly, while the misfit degree remained almost the same. The analysis of the magnetic data shows that the Cobalt ions are coupled antiferromagnetically within the CoO2 layers, with the existence of mixed valence states between Co3+ and Co4+ ions. Besides that, the effective magnetic moments of Cobalt ions are almost constant along the Y doping content. Assuming the orbital quenching as commonly found in most transition metal ions, the data are best fitted by taking the low-spin state of Co3+ ions and intermediate spin state of Co4+ ions. We argue qualitatively, that the spin-state transition across the gap are induced by the shrinkage of the charge transfer energy gaps between O 2p and Co g e levels due to reduction of the ionic spaces between Co and O ions.